Enhanced Immunogenicity of a Genetic Chimeric Protein Consisting of Two Virulence Antigens of Streptococcus mutans and Protection against Infection - Zhang, Ping (American Society for Microbiology, 2002)
The saliva-binding region (SBR) of the cell surface antigen I/II (AgI/II) and the glucan-binding region (GLU) of the glucosyltransferase enzyme of Streptococcus mutans have been implicated in the initial adherence of S. mutans to saliva-coated tooth surfaces and the subsequent sucrose-dependent accumulation of S. mutans, respectively. Here, we describe the construction and characterization of a genetic chimeric protein consisting of the two virulence determinants SBR and GLU (SBR-GLU). The effectiveness of this construct in inducing mucosal and systemic immune responses to each virulence determinant following intranasal immunization was compared to that of each antigen alone or an equal mixture of SBR and GLU (SBR+GLU) in a mouse model. Furthermore, the ability of antibodies induced to SBR-GLU to protect against S. mutans infection was also investigated. Immunization of mice with the chimeric protein SBR-GLU resulted in significantly enhanced (P < 0.001) levels of serum immunoglobulin G (IgG) anti-SBR antibody activity compared to those in the SBR and SBR+GLU groups. The SBR-GLU-immunized mice also demonstrated a significant (P < 0.05) increase in salivary and vaginal IgA antibody responses to SBR and GLU. Analysis of the serum IgG subclass responses to SBR in mice immunized with SBR alone indicated a mixed IgG1 and IgG2a response. A preferential IgG1 response compared to an IgG2a anti-GLU response was induced in mice immunized with GLU alone. Similarly, a preferential IgG1 response was also induced to SBR when GLU was present in either a mixed or conjugated form. Finally, a significant reduction (P < 0.05) in S. mutans colonization was observed only in mice immunized with the SBR-GLU chimeric protein. Taken together, our results indicate that the chimeric protein SBR-GLU significantly enhanced mucosal immune responses to SBR and GLU and systemic immune responses to SBR. The ability of SBR-GLU to induce responses effective in protection against colonization of S. mutans suggests its potential as a vaccine antigen for dental caries.